Update on direct embryo transfer in sheep: hatched blastocysts increase conception rates - Ciornei, Ștefan Gregore (Frontiers in Veterinary Science, 2026)
This article presents an overview of the update on direct embryo transfer using hatched blastocysts. Recent research has observed differences in conception rates in sheep following surgical transfer. All sessions included in the study followed the same standard protocol, resulting in the creation of two groups, with the control group (CG) being the one in which blastocysts were transferred, and the experimental group (EG) received hatched blastocysts. Embryos were obtained from meat sheep through in vivo derived (IVD) and transferred to crossbred sheep synchronized with very obvious corpus luteum (CL) on at least one of the ovaries (84.21%). Thus, a retrospective study highlights the clear success of embryo recipients who also received hatched blastocysts (code 9.1) compared to recipients with blastocysts only (code 6.1, 7.1). The embryo recovery rate at 6.5 days, determined by laparoscopic uterine flushing, was 84.3%. In terms of the quality of the embryos obtained, over 74.5% were transferable (not statistically significant, 76.6% in Suffolk and 72.3% in Ille de France), and over 12% of the embryos hatched. The study found that the pregnancy rate in recipient ewes receiving code 9.1 embryos (expanded blastocysts) through direct IVD transfer during the breeding season was 86.9%. These findings, when compared to previous research, highlight the potential for further exploration and innovation in this area. Nonetheless, it is important to note that there is a scarcity of literature addressing the direct transfer of IVD embryos with expanded blastocysts.